The Other One : Stories. - Sirisena, Hasanthika (Juniper Prize for Fiction., 2016)
"Winner of the Juniper Prize for Fiction. Set in Sri Lanka and America, the ten short stories in this debut collection feature characters struggling to contend with the brutality of a decades long civil war while also seeking security, love, and hope. The characters are students, accountants, soldiers, servants. They are immigrants and strivers. They are each forced to make sometimes comic, sometimes tragic, choices. What they share, despite what they've endured, is the sustaining power of human connection"--